1972
DOI: 10.1002/1097-0142(197210)30:4<889::aid-cncr2820300405>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated aneuploidy: Loss of Y chromosome from human bone marrow cells with aging

Abstract: Direct bone marrow chromosome studies were carried out on 165 males, 3 months to 94 years of age. Forty‐one males were found to have 45,X cell lines in their bone marrow. The number of males exhibiting Y chromosome loss correlated with age, but the degree of Y chromosome loss did not correlate with age. The loss of Y chromosome appears to be a permanent event. The longest follow‐up period in this study was 13 months. The incidence of 45,X cell lines in the bone marrow is much greater than that in peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
2
2

Year Published

1974
1974
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(101 citation statements)
references
References 11 publications
7
90
2
2
Order By: Relevance
“…Interestingly, in the "normal" individuals with loss of the Y chromosome, the frequency of 45,XO cells is also reported to be much lower in the peripheral blood than in bone marrow (2,3). The reason for this finding was thought to be the fact that the major dividing cells in peripheral blood are lymphocytes, whereas in bone marrow, they are myeloid cells (2,12). In the present patient, this assumption seems feasible because the frequency of 45,XO cells in bone marrow was only 20% on stimulation with PHA, a stimulant of lymphocyte growth.…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, in the "normal" individuals with loss of the Y chromosome, the frequency of 45,XO cells is also reported to be much lower in the peripheral blood than in bone marrow (2,3). The reason for this finding was thought to be the fact that the major dividing cells in peripheral blood are lymphocytes, whereas in bone marrow, they are myeloid cells (2,12). In the present patient, this assumption seems feasible because the frequency of 45,XO cells in bone marrow was only 20% on stimulation with PHA, a stimulant of lymphocyte growth.…”
Section: Introductioncontrasting
confidence: 53%
“…One recent finding of interest is that the gene for the granulocyte-macrophage colony stimulating factor receptor (GM-CSFR) was found to be located on the sex chromosomes (10 blood cells showed 45,XO. Interestingly, in the "normal" individuals with loss of the Y chromosome, the frequency of 45,XO cells is also reported to be much lower in the peripheral blood than in bone marrow (2,3). The reason for this finding was thought to be the fact that the major dividing cells in peripheral blood are lymphocytes, whereas in bone marrow, they are myeloid cells (2,12).…”
Section: Introductionmentioning
confidence: 99%
“…However, fingerprint and chromosomal analysis revealed that these lines are quite different. Although no Y chromosome was detected in the prostate-derived cells, it has been observed that the Y chromosome is sometimes lost in malignant cells or in cells from elderly men (Pierre & Hoagland, 1972 (van Helden & Wiid, 1987;van Helden et al, 1988, and unpublished observations). This was also observed in fingerprints obtained from this line over a period of 6 months in continuous culture.…”
Section: Dcosmentioning
confidence: 95%
“…Amongst eutherian mammals X chromosome elimination from some female somatic tissues occurs in Akodon azarae, Acomys selousiand Choloepus hoffmani, while somatic elimination of one X chromosome of fefl}ales and of the single X of male germ cells occurs in Microtus oregoni [see White (1973) for review and references]. Y chromosome elimination has been reported to occur in some cells from somatic tissues in man (Pierre and Hoagland 1972) and murine opossum, Marmosa mitis (Curcuru-Giordano et al 1974).…”
Section: Introductionmentioning
confidence: 99%